ANALISIS GAYA KEPEMIMPINAN ISLAMI KEPALA SEKOLAH PADA SEKOLAH SATIT PHATNAWITYA SCHOOL YALA THAILAND - Nurjannah, Nurjannah; Isra, Isra Hayati (Berajah Journal, 2024)
This research aims to analyze the Islamic leadership style applied by the Principal at Satit Phatnawitya School Yala, Thailand. The research method used is a qualitative approach using in-depth interviews, observation and document analysis as data collection techniques. This research involved the principal, teachers and administrative staff as the main informants. Data analysis was carried out by detailing key aspects of the Islamic leadership style, including justice, honesty, responsibility and concern for school members. Apart from that, this research also explores the impact of this Islamic leadership style on the school environment and teacher performance.The results of the research show that the principal of Satit Phatnawitya School Yala Thailand has implemented an Islamic leadership style for students and teaching staff in the school environment, this is proven by the implementation of activities such as the obligation to pray five times a day for students and teachers, the formation of halaqah or organized associations. This aims to strengthen relationships between teaching stars, implement qiyamul lail which aims to create a positive atmosphere in the school environment, and establish Islamic Islamic studies as a forum for teachers to deepen Islamic studies.